Harmonizing the United Nations action decades for water and nutrition - Oenema, Stineke (2020)
BACKGROUND OF THE WATER AND NUTRITION DECADES International Decade (2018-2028) for Action - Water for Sustainable Development Following the success of the “Water for Life” Decade (2005-2015) Concerns about water safety and water disasters related to climate Water stated as critical to eradicate hunger and poverty Decade of Action on Nutrition (2016-2025) Lack of progress in achieving food and nutrition security Aims to accelerate the implementation of ICN2 recommendations SDG 2 and 3 are central, SDG 6 is included